Modelling of boat acceleration - Kleshnev, V. (BioRow, 2023)
During our BioRow data analysis and feedback, we present target curves for force, blade work and body segment velocities (RBN 2017/2, 2018/3-4). Coaches and rowers sometimes ask: "Why are targets for the boat acceleration curve are not presented?".